b - Imeada, Yoshiro (b, 2013)
Most Bhutanese know Zhabdrung Ngawang Namgyel as a religious leader and the founder of the Bhutanese nation. Yoshiro Imadea's compelling and holistic portrayal of this highly accomplished religious master and shrewd political leader offers a rarely explored aspect of the most important historical figure in Bhutan.
Includes bibliographical references (pages 111-112).
Keywords: Buddhism and state -- History. -- Bhutan